Microtubules Stabilization by Mutant Spastin Affects ER Morphology and Ca2+ Handling - Vajente, Nicola; Norante, Rosa; Redolfi, Nelly; Daga, Andrea; Pizzo, Paola; Pendin, Diana (Frontiers in Physiology, 2019)
The endoplasmic reticulum (ER) extends as a network of interconnected tubules and sheet-like structures in eukaryotic cells. ER tubules dynamically change their morphology and position within the cells in response to physiological stimuli and these network rearrangements depend on the microtubule (MT) cytoskeleton. Store-operated calcium entry (SOCE) relies on the repositioning of ER tubules to form specific ER-plasma membrane junctions. Indeed, the tips of polymerizing MTs are supposed to provide the anchor for ER tubules to move toward the plasma membrane, however the precise role of the cytoskeleton during SOCE has not been conclusively clarified. Here we exploit an in vivo approach involving the manipulation of MT dynamics in Drosophila melanogaster by neuronal expression of a dominant negative variant of the MT-severing protein spastin to induce MT hyper-stabilization. We show that MT stabilization alters ER morphology, favoring an enrichment in ER sheets at the expense of tubules. Stabilizing MTs has a negative impact on the process of SOCE and results in a reduced ER Ca2+ content, affecting the flight ability of the flies. Restoring proper MT organization by administering the MT-destabilizing drug vinblastine, chronically or acutely, rescues ER morphology, SOCE and flight ability, indicating that MT dynamics impairment is responsible for all the phenotypes observed.